Reading Amenk: The Grotesque Aesthetics of Reality - Agung, Lingga; Bastari, Rendy Pandita; Gumilar, Ganjar; Lionardi, Angelia; Siswanto, Riky Azharyandi (Humanus, 2024)
In contemporary art, aesthetics serves as a medium for conveying complex societal and cultural messages. One artist who has masterfully harnessed this power is Mufti Priyanka (Amenk). His body of work is characterized by a unique and intriguing “grotesque aesthetics” that delves into various dimensions of everyday life. Through his art, Amenk provokes profound inquiries into the intricacies of our social realities. This research is dedicated to unraveling the aesthetics intricately woven into Amenk’s artworks, which seemingly offer genuine insights into the collective consciousness of a society grappling with the complexities of social norms and cultural identity. This study adopts a qualitative approach, examining Amenk diverse portfolio, encompassing paintings and graphics. Anchored in the framework of Derrida’s Deconstruction theory (1967), this approach involves a textual analysis, dissecting the conceptual distinctions that form the foundation of the text. By unveiling the inconsistencies and paradoxes inherent in the utilization of these concepts, the research sheds light on the intricate tapestry of Amenk’s artwork. Ultimately, Amenk’s body of work represents more than an exploration of cultural significance; it stands as a bold challenge to established norm, values, and even the truths.